2014
DOI: 10.1002/jgt.21819
|View full text |Cite
|
Sign up to set email alerts
|

A Proof of a Conjecture of Ohba

Abstract: We prove a conjecture of Ohba that says that every graph G

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
(51 reference statements)
0
41
0
Order By: Relevance
“…Therefore, χ(GD)=k. Furthermore, it is easy to see that GD satisfies the condition stated in Theorem , since: false|Vfalse(GDfalse)false|=false|Vfalse(Dfalse)false|2χfalse(Dfalse)+1=2k+1=2χfalse(GDfalse)+1.Hence, χfalse(GDfalse)=χfalse(GDfalse)=k since Theorem is verified . Now consider any k ‐list‐assignment L to D .…”
Section: Ohba's Conjecture For Digraphsmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, χ(GD)=k. Furthermore, it is easy to see that GD satisfies the condition stated in Theorem , since: false|Vfalse(GDfalse)false|=false|Vfalse(Dfalse)false|2χfalse(Dfalse)+1=2k+1=2χfalse(GDfalse)+1.Hence, χfalse(GDfalse)=χfalse(GDfalse)=k since Theorem is verified . Now consider any k ‐list‐assignment L to D .…”
Section: Ohba's Conjecture For Digraphsmentioning
confidence: 90%
“…In [15], Ohba conjectured that the equality = should hold for every undirected graph with relatively small order (compared to their chromatic number). Ohba's conjecture was recently proved in [22] by Noel, Reed, and Wu. Theorem 2.1 (Ohba's conjecture).…”
Section: Ohba's Conjecture For Digraphsmentioning
confidence: 94%
“…The coloring algorithm, which we call Painter, must choose an independent set of marked vertices to receive that color. Colored Ohba [11] conjectured that G is chromatic-choosable when |V (G)| ≤ 2χ(G) + 1; after partial results in [8,11,12,14], this was proved by Noel, Reed, and Wu [10]. Various researchers (see [7]) observed that the complete multipartite graph K 2,...,2,3 is chromatic-choosable but not chromatic-paintable, so the paintability analogue is slightly different: Conjecture 1.2.…”
Section: Introductionmentioning
confidence: 98%
“…Quite recently, Ohba's conjecture has been verified by Noel et al [6] with a complicated proof. However, it seems difficult to apply their method to handle the conjecture of Zhen and Wu mentioned above.…”
mentioning
confidence: 94%